STRATEGIC DIAGNOSIS OF LIVESTOCK-FOREST INTEGRATION SYSTEMS IN NORTHERN MATO GROSSO - Ansolin, Roni Djeison; Timofeiczyk Junior, Romano; Garzel Leodoro da Silva, João Carlos; Michetti, Miquéias; Takahashi Kamoi, Mariana Yumi; dos Reis, Julio Cesar (Floresta, 2019)
The objective of this study was to elaborate a strategic diagnosis about integrating the forest component (teak) into extensive cattle raising areas, in Alta Floresta, northern Mato Grosso state. For this, the SWOT analysis consisted of initially identifying the internal factors, the strengths and weaknesses internal to the organization (interviews) and the external factors, opportunities and threats external to the organization (bibliographic search) to elaborate the External and Internal Factor Evaluation Matrices. The data were obtained from applying semi-structured interviews to some of the key players in the agro-industrial chain, such as (3) producers, (3) farm managers, (2) professional technicians from the livestock field, and (3) collaborators of public institutions, and a bibliographic search/review as well. The answers given by each interviewee were scored according to their relevance. The scores assigned to internal and external factor evaluations were 2.83 and 3.24, higher than the average 2.5, indicating that the integration of forest with pasture areas is internally strong while the studied region has a favorable external environment. In general, the produced diagnosis indicates that the integration of livestock-forest is an attractive activity, promoting production diversity and collaborating with local development. However, there must be strategic planning between the different key players (government, public and private sectors) in order to foster the most appropriate activities for the region, guaranteeing the conditions for the consolidation of the forest-livestock integration system, given its great potential in relation to monoculture systems.